Factors Affecting Work life Balance of the Area Revenue Branch Officers in the Revenue Office Regional 9 - Mapanao, Siriwan; Surapoppisith, Piyamas (Journal of Management Science Nakhonratchasima University, 2023)
The research entitled “Factors affecting the work-life balance of revenue officers in the Regional Revenue Office 9” was objected to 1) study the work factors 2) study the level of work-life balance and 3) study the work factors affecting the work-life balance. The data was collected from a sample group of 300 revenue officers by using the questionnaires as a research tool. The statistics, used in the data analysis, were included with the frequency, the percentage, Mean, Standard Deviation and Multiple Regression. The results of the study revealed that most of the samplings were female, aged between 31-40 years, single, and being civil servants with a working period of 1-10 years. For the work factors, it was found overall that the monthly income, the job security and the relationships with co-workers were at a high level. The factors most affected the work were the relationship with co-workers. Moreover, the work-life balance in 5 categories; the work, the family, the life time, the finances, and the knowledge development, were overall at a high level. In addition, the work factor had the highest work-life balance. It was also found that all 3 work factors statistically significant affected the work-life balance.